A short review on the recent progress and properties of pineapple leaf fiber reinforced composite - Hameed Sultan, Mohamed Thariq; Hanyue, Xiao; Shahar, Farah Syazwani; Najeeb, Muhammad Imran (E3S Web of Conferences, 2024)
Because of the increase in demand and the enhancement of environmental awareness, researchers are committed to the research and development of innovative, high-performance, and low-cost green materials, especially since there is a large amount the study of natural fiber reinforced composite materials. An abundance of waste of pineapple leaves in Malaysia every year. If pineapple leaf fibers (PALF) can be extracted from the waste of pineapple leaves and made into green composites, it can not only solve the agricultural waste but also produce environment-friendly green composite materials to be applied in related industries. The main purpose of this review is to give an overview of recent developments in PALF reinforced composites as well as their properties. In this short review, the characteristics of PALF and its composites, the mechanical properties and the environmental impact of PALF reinforced composite are studied. In the future, with the increasing research on PALF, selection of different composite materials and design of appropriate structures, the performance of PALF reinforced composites will significantly be improved, and thus has great potential to be widely used in product production and manufacturing.